2011
DOI: 10.1080/19415257.2011.576262
|View full text |Cite
|
Sign up to set email alerts
|

The professional development of teacher identities in Hong Kong: can a short-term course make a difference?

Abstract: This article reports on a qualitative study that explored the experiences of eight Hong Kong teachers of academic subjects who undertook a full-time, short-term professional development course (PDC) designed to provide them with specialized knowledge and classroom skills required to teach content subjects through the English medium. Using a theoretical framework for understanding teacher identity, the study examined how these eight teachers believed the experiences of a short-term PDC shaped their ongoing iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 22 publications
0
21
0
1
Order By: Relevance
“…Students identified actors in teacher education in order of their areas of 'specialism', 'teacher' and 'student'. Most lecturers were conscious of their position(ing) (Trent, 2011) from the beginning of the conversations. For example, L3 describes himself as lecturer teaching citizenship education.…”
Section: How Participants Described Their Identitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Students identified actors in teacher education in order of their areas of 'specialism', 'teacher' and 'student'. Most lecturers were conscious of their position(ing) (Trent, 2011) from the beginning of the conversations. For example, L3 describes himself as lecturer teaching citizenship education.…”
Section: How Participants Described Their Identitiesmentioning
confidence: 99%
“…She talked about others lacking the 'right' qualifications. Such a perceived identity seem to suggest giving oneself a more privileged position (Trent, 2011) than the rest of the lecturers or 'us and them' division (Maclure, 2003;Trent, 20011). A commonly used identity of lecturer like L7 was science educator, emphasizing specialism in science.…”
Section: How Participants Described Their Identitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Amid the economic, managerial, technological, and societal challenges of the 21st century, work organizations, including those in education and health care, are increasingly expected to develop their management practices, work culture, and operations in order to provide high-quality and innovative services, including teaching and research (Billett 2011. At the same time, changing work practices and organizational structures impose strong demands on employees, who are required to develop their professional competencies and practices, cross traditional professional boundaries, re-construct professional relationships, negotiate their career, and transform their professional identity (Brown et al 2007, Kira and Balkin 2014, Shagrir 2010, Trent 2011. For example, the pressures to engage more actively in research have challenged academics to craft their professional identity, moving from teaching towards research (Hökkä and Eteläpelto 2014, Willemse et al 2015, Ylijoki and Ursin 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Additional research has correlated the use of investigation and reflective practices with the development of teachers' professional consciousness (Jacobs, Assaf, and Lee 2011;Lee 2009;Snoek and Moens 2011;Stanulis and Ames 2009;Trent 2011), the improvement of student outcomes (Crippen et al 2010;Davies 2010) and improvements in the teaching procedure (Langdon 2011;Pedder and Opfer 2011;Strand and Bosco-Ruggiero 2011). The specific investigation and research practices suggested in the above articles included the following: the individual trial and testing of different practices during the teaching procedure; the trial and testing of different practices in collaborative communities of practice with the aim of enhancing the teaching procedure; the regular collection of data on the progress of the children by their teachers in relation to the educational methods and practices that teachers used; the use of portfolios and other reflective tools; and dialogue between the educators on different educational issues based on the data collected.…”
Section: Introductionmentioning
confidence: 99%